2009
DOI: 10.2478/v10001-009-0006-7
|View full text |Cite
|
Sign up to set email alerts
|

Ambient sulphur dioxide exposure and emergency department visits for migraine in Vancouver, Canada

Abstract: Objectives: Ambient exposure to sulphur dioxide (SO 2 ) has been previously associated with emergency department (ED) visits for migraine headaches. In the present study, the objective was to examine the relationship between ED visits for migraine and ambient sulphur dioxide concentrations. Design and Methods: This was a time-series study of 1 059 ED visits for migraine (ICD-9: 346) recorded at a Vancouver hospital between 1999 and 2003 (1 520 days). Air pollution levels of SO 2 were measured by fixed-site mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 17 publications
2
29
1
Order By: Relevance
“…It has also been linked to nervous system disorders such as stroke and headache [16,17]. Cakmak et al have demonstrated the positive relationship between SO 2 and epilepsy [12], which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been linked to nervous system disorders such as stroke and headache [16,17]. Cakmak et al have demonstrated the positive relationship between SO 2 and epilepsy [12], which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…For each air pollution variable we have 24 measurements recorded at hourly intervals. These include data on gaseous pollutants: SO 2 , carbon monoxide (CO), nitrogen oxide (NO 2 ), ozone (O 3 ), and particulate matter data: respirable particles PM 2.5 and inhalable PM 10 , particulate matter of median aerodynamic diameter less than 2.5 and 10 microns, respectively. The daily shared exposures of the population were expressed as mean values among stations in city (Table 2).…”
Section: Air Pollution Datamentioning
confidence: 99%
“…For each lagged values a separate model was constructed. Our analysis represents the percentage value of changes in relative risk (%RR) with 95% confidence intervals (CI) associated with an increase in average of pollutant concentrations of the exposure to the study pollutants (SO 2 , NO 2 , CO, O 3 , PM 10 , and PM 2.5 ) after adjusting for temperature and relative humidity. Estimates whose 95% CI do not cross 0 are considered significant.…”
Section: O R I G I N a L P A P E R S Ijomeh 2009;22(3) 237mentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies imply that SO 2 exposure not only induced many respiratory responses (Schwela, 2000;Herbarth et al, 2001), but linked with many neurological disorders such as migraine headaches, stroke, and brain cancer (Andersson et al, 1998;Hong et al, 2002a;Tsai et al, 2003;Szyszkowicz et al, 2009). SO 2 is a gas and exists in aqueous solution at neutral pH as an equilibrium between bisulfite and sulfite ions (NaHSO 3 and Na 2 SO 3 , 3:1 M/M), which was defined as SO 2 derivatives (Shapiro, 1977;Meng et al, 2004;Du et al, 2006).…”
Section: Introductionmentioning
confidence: 98%